Pengaruh Gaya Kepemimpinan terhadap Organizational Citizenship Behavior di PT. Angkasa Pura II Bandar Udara Supadio Pontianak - Selly Tasya Mauli Marbun (Institut Teknologi dan Bisnis (ITB) Semarang, 2023)
The attitude or behavior of employe affects the success in carrying out tasks in an organization. Employee behavior is divided into two, namely in-role and extra-role. Extra-role behavior in an organization is also known as Organizational Citizenship Behavior (OCB). Organizational Citizenship Behavior (OCB) is extra behavior that is not part of an employee's formal work obligations, but supports the effective functioning of the company. This study aims to determine the influence and how much influence the leadership style has on OCB. This research is a research that uses quantitative methods with data collection techniques using questionnaires distributed through the Google Form. The sample used in data collection was 80 employees from the Airside Operation, Airport Security/Aviation Security, and Operational Airport and Service Terminal units at Supadio Pontianak Airport. The results of the study show that Leadership Style has a significant effect on Organizational Citizenship Behavior. These results are proven by the tests that have been carried out, namely it was found that the t-value of 31.763 is greater than the t-table value of 1.664. Through the test of the coefficient of determination, it was found that Leadership Style influences OCB by 92,8%.